Kajian Rijal al-Hadis dan Jarh wa al-Ta'dil: Metodologi Verifikasi Perawi dalam Tradisi Keilmuan Hadis - Nadianti Yanti; Sarmin; Zaenab (STKIP Subang, 2026)
This article examines the discipline of Rijal al-Hadith and Jarh wa al-Ta'dil as the cornerstone of hadith authentication in classical Islamic scholarship. These two interrelated sciences constitute the primary instrument through which Muslim scholars have historically evaluated the credibility and reliability of hadith transmitters. The study employs a qualitative library research method, drawing upon classical hadith literature and contemporary academic sources. The findings reveal that Rijal al-Hadith encompasses a comprehensive biographical methodology including the tabaqat system, chain-of-transmission verification, and comparative narration analysis, while Jarh wa al-Ta'dil provides a hierarchical grading framework that assesses narrators across six levels of acceptance and six levels of rejection. The two sciences are governed by rigorous criteria including Islam, legal majority, soundness of mind, moral uprightness ('adalah), and reliability of memory (dhabt). Major reference works such as Al-Tabaqat al-Kubra, Al-Tarikh al-Kabir, and Tahdzib al-Kamal have served as indispensable tools for hadith scholars across generations. The article concludes that these methodological frameworks remain relevant in contemporary Islamic scholarship and offer applicable models for credibility assessment in the age of digital information.